Two periplasmic transport proteins which interact with a common membrane receptor show extensive homology: complete nucleotide sequences. - Higgins, C F (1981)
The hisJ and argT genes of Salmonella typhimurium encode two periplasmic binding proteins, J and LAO, which are involved in histidine and arginine transport, respectively, and which interact with a common membrane-bound component, the P protein. The complete nucleotide sequences of these two genes have been determined. The two genes show extensive homology (70%) and presumably arose by tandem duplication of a single ancestral gene. The two encoded proteins now perform distinct functions but still retain sufficient homology to permit interaction with the same site on the membrane-bound P protein. Three lines of evidence have allowed both the amino acid-binding site and the site involved in the interaction with the P protein to be assigned to specific regions of each binding protein: (i) the distribution of amino acid differences between the two proteins; (ii) the properties of a functional chimeric protein, produced by a deletion mutant in which the first half of the argT gene is fused to the second half of the hisJ gene; (iii) the sequence change in a mutant J protein unable to interact with P.